Kedisiplinan dan Motivasi Kerja, Pengaruhnya Terhadap Kinerja Pegawai Kecamatan - Nurdiana; Harenal Daeng Toto; Masradin Masradin; Bahriansyah Bahriansyah; Ahmad Yani Abdurrahman (LP2M IBK Nitro, 2022)
The purpose of this study was to analyze the relationship between discipline and motivation on employee performance in Bontomate'ne District and Bontoharu District, Kab. Selayar Islands. The data used are primary data and secondary data. Data was collected through questionnaires and documentation. The data analysis method used descriptive statistical analysis and multiple linear regression analysis. Simultaneous test results show that discipline and motivation variables have a significant effect on employee performance, while partial test results show that discipline and motivation variables have a significant effect on employee performance.